2021
DOI: 10.3390/jcs5100262
|View full text |Cite
|
Sign up to set email alerts
|

Carbonization Temperature and Its Effect on the Mechanical Properties, Wear and Corrosion Resistance of Aluminum Reinforced with Eggshell

Abstract: In this paper, the effect of the carbonization temperature on the mechanical properties, density, wear and corrosion resistance of AA 6063 reinforced with eggshells was investigated. The selected fabrication route for this investigation was stir casting while the weight fraction of the eggshells was kept constant at 5 wt.%. The carbonization temperature was varied at 900, 1000, 1100, and 1200 °C. The microstructure revealed that the eggshells were fairly uniformly dispersed on the individual grains and along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Although this article does not consider the mechanical properties in the experimental methodology, the results obtained show an improvement in the thermal-chemical properties of the resultant composites that can positively affect their mechanical properties. Previous studies have shown similar findings in that the mechanical properties can be improved alongside good dispersion of the filling materials and an improvement in the thermal properties [8,19,21].…”
Section: Chemical Analysis By Ftirsupporting
confidence: 60%
See 1 more Smart Citation
“…Although this article does not consider the mechanical properties in the experimental methodology, the results obtained show an improvement in the thermal-chemical properties of the resultant composites that can positively affect their mechanical properties. Previous studies have shown similar findings in that the mechanical properties can be improved alongside good dispersion of the filling materials and an improvement in the thermal properties [8,19,21].…”
Section: Chemical Analysis By Ftirsupporting
confidence: 60%
“…Such a cheap and sustainable material as waste ES can definitely help in reducing costs and minimizing the environ-mental pollution caused by waste eggshells and petroleumbased polymers [19,20]. Additionally, the implementation of these new biobased reinforcing materials into the structure of polyamide 12 matrix can broaden the scope of PA applications in various sectors, including industries that manufacture interior parts for automobiles, aircraft, and aerospace.…”
Section: Introductionmentioning
confidence: 99%
“…The impact energy absorbed by the composites is also presented in Figure 7. Composite EC3 (5 wt.% eggshells) gives the highest impact energy value, at the same time, composite EC1 (0 wt.% eggshell) shows the most bass impact energy value [26]. The order of impact energy is 11 J ˂ 13 J ˂ 14.5 J ˂ 16.5 J for the EC1, EC4, EC2, and EC3 composites, respectively.…”
Section: Hardness and Impact Strength Of Fabricated Compositesmentioning
confidence: 93%
“…Moreover, carbonized eggshell powder gives better mechanical properties than un-carbonized eggshell powder reinforced composites. Other authors [24][25][26] also successfully utilized eggshell powder as reinforcement in different aluminium alloys and found an improvement in composites' mechanical and wear behavior. The composite material created by incorporating different filler materials into the AA6061 matrix has better mechanical characteristics than the original aluminium alloy in terms of strength, and stiffness [25].…”
Section: Sb Hassan Et Al [23] Fabricated Compositesmentioning
confidence: 99%